Influence of Acute Eccentric Exercise on the H:Q Ratio - Thompson, B. J.; Smith, D. B.; Sobolewski, E. J.; Fiddler, R. E.; Everett, L.; Klufa, J. L.; Ryan, E. D. (International Journal of Sports Medicine, 2011)
The purpose of the present study was to examine the effects of an acute bout of eccentric exercise on maximal isokinetic concentric peak torque (PT) of the leg flexors and extensors and the hamstrings-to-quadriceps (H:Q) strength ratio. Sixteen male (mean±SD: age=20.9±2 years; stature=177.0±4.4 cm; mass=76.8±10.0 kg) volunteers performed maximal, concentric isokinetic leg extension and flexion muscle actions at 60°·sec − 1 before and after (24–72 h) a bout of eccentric exercise. The eccentric exercise protocol consisted of 4 sets of 10 repetitions for the leg press, leg extension, and leg curl exercises at 120% of the concentric one repetition maximum (1-RM). The results indicated that the acute eccentric exercise protocol resulted in a significant (P<0.05) decrease in isokinetic leg flexion (13–19%) and leg extension (11–16%) PT 24–72 h post-exercise. However, the H:Q ratios were unaltered by the eccentric exercise protocol. These findings suggest that an acute bout of eccentric exercise utilizing both multi – and single – joint dynamic constant external resistance (DCER) exercises results in similar decreases in maximal isokinetic strength of the leg flexors and extensors, but does not alter the H:Q ratio.
Keywords: hamstring injury risk; hamstrings to quadriceps ratio; muscle strength imbalance